2011
DOI: 10.1097/pai.0b013e318212f027
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Multiplex Immunohistochemistry Using the 4-antibody Cocktail YANA-4 in Differentiating Primary Adenocarcinoma From Squamous Cell Carcinoma of the Lung

Abstract: The current Food and Drug Administration-approved standard treatment for non-small cell carcinomas consists of carboplatin/taxol/avastin. However, nowadays more specialized protocols, depending on tumor subtype, are being used for lung cancer patients. Therefore, accurate differentiation between adenocarcinoma and squamous cell carcinoma is essential for the selection of appropriate therapies. We designed a rapid multiplex immunostaining method using a novel 4-antibody cocktail, YANA-4. This antibody cocktail … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 28 publications
0
24
0
1
Order By: Relevance
“…39 Rather than a step-wise approach proposed here, an alternative method of tissue conservations is the use of antibody cocktails, as recently described. 17,40 While promising, the wide utilization may be limited by availability of these reagents. In contrast, the algorithm described here is widely applicable because it includes conventional well-characterized antibodies, which are available in most pathology laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…39 Rather than a step-wise approach proposed here, an alternative method of tissue conservations is the use of antibody cocktails, as recently described. 17,40 While promising, the wide utilization may be limited by availability of these reagents. In contrast, the algorithm described here is widely applicable because it includes conventional well-characterized antibodies, which are available in most pathology laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…An immunohistochemical antibody, P63, is a sensitive and specific marker for squamous carcinoma of the lung [19][20][21][22][23]. Tumors formerly classified simply as poorly differentiated non-small-cell carcinoma are about as likely to be called adenocarcinoma as squamous carcinoma [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of micro-tissue array sections of lung cancer have shown the value of TTF-1, napsin A, p63 and CK5/6 (3). Yanagita et al (7) reported findings obtained using a cocktail of TTF-1, napsin A, p63, and CK14 antibodies. In this report, the combination of antibodies was useful fordifferential diagnosis; in particular, TTF-1 and napsin A were effective in determining a differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%